Printed thermal hydrogel for ambient energy harvesting - Xie, Jiahua (Nanyang Technological University, 2023)
Waste heat energy recovery using electrochemical/thermogalvanic cells has been gaining popularity due to their potential as a sustainable and cost-effective energy source. When the two electrodes are held at different temperatures, a voltage is generated due to the difference in the electrochemical potentials of the two electrodes. This voltage can be used to power external devices or to store energy in a battery. The efficiency of thermogalvanic cells depends on several factors, including the materials used for the electrodes, the temperature gradient, cell orientation, electrode spacing and the composition of the electrolyte solution. In this report, the author studies the various factors that affect the efficiency of the cell.